(untitled) (Acta Entomologica Serbica, 2015)
Only one species of the genus Callicera Panzer, 1806 - Callicera aenea (Fabricius, 1777) has been recorded in Serbia so far. The first documented records of the Callicera aurata (Rossi, 1790) and Callicera spinolae Rondani, 1844 are provided. Identification keys, material studied and distribution maps for each Serbian species are provided.